Disturbance alters the response of consumer communities towards warming: a mesocosm study with biofilm‐dwelling ciliates. Issue 1 (24th January 2014) - Marcus, Hanna; Wey, Jennifer K.; Norf, Helge; Weitere, Markus
Abstract : Environmental warming can have negative effects on the carrying capacity of communities because metabolic rates increase at the expense of biomass. Here, we tested the hypothesis that such warming effects are reversed in communities experiencing disturbance, as temperature‐driven growth processes gain relevance and can compensate for negative disturbance effects. Model communities of semi‐natural, biofilm‐dwelling ciliates were cultivated in mesocosms (river bypass systems) under two temperature regimes (ambient temperature and increased by 4°C). The interactive effects between these different temperatures and seven disturbance intensities were tested in a nested design. Disturbance generally reduced total ciliate abundances, whereas only small effects on the prevalence of functional diversity were detected. Temperature effects differed between different disturbance intensities and seasons: Whereas warming reduced the carrying capacity of undisturbed communities irrespective of the season, pronounced positive warming effects were detected under disturbance in winter and, to a lesser extent, in spring. Neither significant temperature nor disturbance effects were recorded in summer, probably because ciliate growth rates were not temperature limited due to high summer background temperatures. Our results show that disturbance can markedly alter warming effects on temperature limited communities. Since natural communities commonly face disturbance, it should therefore be considered in models of future environmental warming responses.